Inclusive Policy on Maternal Health is Needed to Attain Sustainable Development Goal (3.1) in Pakistan - Zarif, Adil (International Journal of Pathology, 2023)
Globally, a woman dies every two minutes during pregnancy related causes or during childbirth. This painful fact has been highlighted in a recent report “Trends in Maternal Mortality” by partner UN agencies. The maternal mortality ratio has increased in most parts of the world. Sub-Saharan Africa tops the figure with 70pc fatalities, of which Nigeria accounts for 82,000.1The report tracks maternal deaths globally from 2000 to 2020, has estimated 287 000 maternal deaths worldwide in 2020. This reflects meager decrease from 309,000 in 2016 when Sustainable Development Goals began. The UNFPA executive director termed lack of progress on maternal mortality figure as “unconscionable”.